(untitled) (NAU Journal of Library and Information Science, 2025)
This study examines factors predicting technology-enabled knowledge sharing among Professional and Paraprofessional Librarians (PPLs) in federal universities across South-East Nigeria. A total enumeration technique was employed, involving all 238 PPLs from five federal universities in the region. Data were collected using a validated structured questionnaire, with reliability coefficients of 0.84 for technology availability, 0.75 for perceived ease of use, 0.84 for perceived usefulness, and 0.90 for technology-enabled knowledge sharing. Descriptive statistics addressed research questions, while simple regression analysis tested hypotheses. Findings revealed that technology availability, perceived ease of use, and perceived usefulness positively and significantly predicted technology-enabled knowledge sharing. However, despite the availability of technology, ownership is primarily personal rather than institutional. Ease of use was moderate, as some PPLs struggled with troubleshooting and felt intimidated by technology. A small group perceived technology as unnecessary. Although LIS professionals actively engaged in online discussions and networking, their participation in content creation and structured knowledge-sharing platforms remained low. To address this, the study recommends among others, that the Nigerian Library Association (NLA) and the Librarians Registration Council of Nigeria (LRCN) organize training programmes to enhance librarians’ librarians’ ability to use technology for knowledge sharing as part of their ongoing professional development.